Trace mineral levels during gestation of sows in confinement-effects on immunoglobin performance and health of neonatal pigs - D A Schoneweis; G L Allee (Kansas Agricultural Experiment Station Research Reports, 1976)
We compared the effects of two levels of trace minerals fed dams during gestation on the hemoglobin, packed cell volume, performance, and health of 31 litters of neonatal pigs. The dams had been on concrete all of their lives. There were no significant differences in the hemoglobin or packed cell volume in pigs due to trace mineral levels fed the dam during gestation. There were no apparent differences in the incidence of neonatal disease or other problems in any of the pigs. These results indicate no benefit from adding excess trace minerals to the ration of sows during gestation, even though the sows are in confinement.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Trace minerals; Gestation; Sows; Immunoglobin performance; Neonatal pigs